Activist Scholar-Practitioners in the United States and South Africa (Revista de sociología clínica, 2022)
This article discusses the lives and impact of leading activists whose work is highlighted in the histories of clinical sociology in the United States and South Africa. The four scholar-practitioners from the United States discussed here are Jane Addams, W.E.B. Du Bois, Charles Gomillion and James Laue. The South African clinical sociologists whose lives are profiled are Harold Wolpe and H.W. van der Merwe. Based on the career experiences of these six individuals, concluding comments are made about five topics in relation to activism: employment, sufficient time for effective activism, handling criticism, reasons for becoming strong activists, and factors that may discourage activism.